Identification D’un Substrat Adequat Pour La Germination Du Fuzz De Canne A Sucre (Saccharum officinarum L.) A Ferkessedougou - Zadi, Marcos; Turquin, Louise; Pene, Crépin (European Scientific Journal, ESJ, 2018)
An alternative solution to the importation of high performing varieties, integrating the importation of sugar cane fuzz, and the germination of these followed by a selection would be the beginning of a response to the low competitiveness of Ivorian sugar. In order to identify a substrate for fuzz germination and plant growth, three substrates (TKS1, Biofertil and Ecume) were tested in a 4-repeat blocks factorial device. The TKS1 recognized as effective for the germination of fuzz served as a control. The substrates were compared according to their effects on emergence dynamics, the rate,velocity andtime limit of germination of the SP70 1006 and VMC 96/56 fuzz. The results showed that Biofertil (0.83 ± 0.79 p.c.) and TKS1 (0.9 ± 0.94 p.c.) generated statistically identical germination rates. It is the same for the germination rate where these two substrates had similar effects, respectively 1.11 ± 1.06 fuzz/dand 1.19 ± 1.26fuzz/d. For these two parameters of germination, scum with respectively 0.4 ± 0.83 % and 0.53 ± 0.51 fuzz/dwas less efficient than the two previous substrates. Biofertil could therefore replace TKS1 under the conditions of Ferkessédougou 2.